The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/rlu.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Primary Pancreatic Choriocarcinoma Revealed on FDG PET/CT

Abstract: Choriocarcinoma is a cancer that usually occurs in the uterus during pregnancy. Extragonadal choriocarcinoma, although very rare, can occur. The diagnostic dilatation and curettage of the uterus in a 28-year-old woman who had vaginal bleeding and elevated human chorionic gonadotrophin level failed to identify any abnormality. FDG PET/CT revealed abnormal activity in the head of the pancreas. Pathological examination after partial pancreatectomy demonstrated primary choriocarcinoma in the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Metastatic choriocarcinoma to organs such as the pancreas, lung or brain has been previously reported. 7,9 This current patient was a rare case of sequential GTN metastasis to the liver and subsequently to the pancreas, which was shown by histopathological examinations to be a PSTT after a long period of disease quiescence. The mass in the body of the pancreas was successfully resected and an additional five cycles of monthly chemotherapy were administered.…”
Section: Discussionmentioning
confidence: 76%
“…Metastatic choriocarcinoma to organs such as the pancreas, lung or brain has been previously reported. 7,9 This current patient was a rare case of sequential GTN metastasis to the liver and subsequently to the pancreas, which was shown by histopathological examinations to be a PSTT after a long period of disease quiescence. The mass in the body of the pancreas was successfully resected and an additional five cycles of monthly chemotherapy were administered.…”
Section: Discussionmentioning
confidence: 76%
“…However, a subset of cases has demonstrated low 18 F-FDG accumulation in metastatic nodules from choriocarcinoma, potentially influenced by hemorrhagic and/or necrotic components affecting 18 F-FDG avidity ( 83 ). The reported SUVmax range for choriocarcinoma spans from 2.0 to 27.5, encompassing various studies ( 13 , 16 , 20 , 21 , 23 , 26 , 28 , 30 , 31 , 33 , 36 , 45 – 47 , 49 , 51 , 53 , 54 , 60 62 , 64 , 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GLUT-1 and hexokinase-Ⅱ has been reported in PC [23] . In patients with PC, several studies have demonstrated that 18 F-FDG PET/CT was an important key factor for in staging, detecting postoperative recurrence, and evaluating the response to treatment [24][25][26][27][28] . The recent typical researches and interest findings were listed in the follow.…”
Section: F-fluorodeoxyglucosementioning
confidence: 99%